Relações lógico-semânticas na organização sequencial da argumentação em textos: um estudo sistêmico-funcional - Nunes, Glivia Guimarães (2018)
In their daily routine, people often position themselves about facts of high repercussion at the time. There are, in addition, many discursive genres through which theses positioning are expressed, such is the case of the opinion article, the open letter and the editorial, all of them belonging to the media context. In such genres, authors employ arguments which ground their point of view (thesis), and lexicogrammatical items are used to articulate the arguments to the positioning and the arguments to each other. These connections happen, thus, from the meaning relations. Starting from this idea, this work aims to analyze how the logico-semantic relations operate in the sequential organization of argumentation in argumentative genres published in the Brazilian media context. Therefore, we count on the theoretical contribution of Systemic Functional Linguistics (HALLIDAY; MATTHIESSEN, 2004; 2014), more specifically of its analytical tool, the Systemic Functional Grammar, through the logico-semantic relations of the clause complex. These relations are organized in two systems, expansion and projection, which are intertwined with the tactical systems, parataxis and hypotaxis. The expansion involves the categories of extension, elaboration and intensification; the projection encompasses the locution and the idea. Each of these categories of logico-semantic relations comprehends other specific ones. In addition, these study has the theoretical background of argumentation approaches (PERELMAN; OLBRECHTS-TYTECA, 2014; REBOUL, 1998; among others), genres (BAKHTIN, [1992] 2011), mainly on Socio-Rhetorical perspective (MILLER, 1984; BAZERMAN, 2005; among others) and argumentative genres, more specifically those which compose the corpus: opinion articles (RODRIGUES, 2005; COSTA, 2008; among other), open letters (FUZER; GONÇALVES, 2016; SILVA, 2002; among others) and editorials (MELO, 1994; ALVES FILHO, 2006; among others). In this sense, the corpus is formed by forty five texts (fifteen opinion articles, fifteen open letters and fifteen editorials) published on Brazilian communication vehicles between March and September of 2016, the texts are on the Dilma Rousseff‘s impeachment, a theme of high repercussion during this period. For the study‘s development, it was carried out a qualitative research with a quantitative support, whose analysis was organized in three steps: contextual (investigation about the contextual configuration of texts), textual (identification of thesis and arguments and categorization, accounting and systematization of the logico-semantic relations which bound them) and interpretative-semantic (interpretation of data, verification of contribution of these recurrent relations for the argumentation in genres). Results show that the majority of texts present arguments with nesting structures inside them (phenomenon called ―nesting‖, in this work), as well as the prevalence of expansion relations in all the genres, mainly those of intensification and extension. In the articulation between arguments and thesis, it is more common the intensification relations, mainly of cause:reason; on the other hand, among arguments there is the prevalence of extension relations, specially positive and opposite additives, followed by those of intensification. Therefore, it is evident the authors‘ concern about the justification of thesis‘ choice, presenting arguments which substantiate it, as well as with making the argumentation progress, aiming, essentially, the insertion of new information which is added or contrasted to the previous one or, still, which serves to circumstantiate them, in terms of cause:reason predominantly.